PENGARUH METODE PEMBAYARAN KOMPENSASI TERHADAP KINERJA TUTOR - Ariandi, Fajri (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2018)
SG cibubur alternativ learning guidance in improving the performance of the tutor should pay attention to severalways, one of the most important thing is compensation. A good compensation pay mentmethod will have an impacton the performance of the tutor. If the performance of the tutor is good then it will have a good impact also in the quality of learning guidance agencies. At this time the method of payment of compensation using the transfer system. The payment with the transfer system has some disadvantages compared to the payment method of cash payment system implemented in the period until 2016. Therefore with this research may be able to provide a solution which the method of payment of compensation is the most ideal tutor for the tutor.Keywords: Compensation, Performance, Tutor